Intra-individual reaction time variability in schizophrenia, depression and borderline personality disorder - Kaiser, Stefan; Roth, Alexander; Rentrop, Mirjam; Friederich, Hans-Christoph; Bender, Stephan; Weisbrod, Matthias (Brain and cognition, 2008)
Intra-individual reaction time variability (IIV) in neuropsychological task performance reflects short term fluctuations in performance. Increased IIV has been reported in patients with schizophrenia and could be related to a deficient neural timing mechanism, but the role of IIV in adult patients with other psychiatric disorders has not been established. Therefore, we compared IIV measures obtained in a Go/Nogo task from patients with schizophrenia, major depression and borderline personality disorder. IIV was increased for patients with schizophrenia. When correcting for differences in mean reaction time, depressive and borderline patients also showed increased IIV. Importantly, all groups showed a strong association between IIV and accuracy of task performance. This suggests that increased IIV might be a sensitive marker for the efficiency of top-down attentional control in all diagnostic groups. Aside from these similarities, the complete results including measures of IIV, mean reaction time and accuracy show differential patterns for patients with schizophrenia compared to those with borderline personality disorder or depression. These results are discussed with respect to common versus disorder-specific neural mechanisms underlying increased IIV.
Available online 2 July 2007
Gesehen am 14.12.2021